Adaptive capacity of the GIAHS territory of Axarquía (Malaga) through Nature-based Solutions - Sillero-Medina, José Antonio; Ruiz-Sinoga, José Damián (Revista de Estudios Andaluces, 2023)
Soil degradation conditions in mediterranean areas make sustainable agricultural activity difficult, especially in a context of global change, where soil loss rates are increased by changes in rainfall dynamics. Thus, the territory designated as an «Important Agricultural World Heritage System» (GIAHS) dedicated to raisins in Axarquía (Malaga) is identified as an area of special vulnerability to these processes. This research aims, on the one hand, to determine the susceptibility to soil erosion and, especially, to find out what role Nature-based Solutions (NbS) are playing in the adaptive capacity of this region. For this purpose, the rainfall dynamics have been statistically analysed, soil erosion rates have been determined using the RUSLE model and, finally, a qualitative methodology for the evaluation of NbS has been developed. The results show a clear decrease in annual rainfall and a concentration of rainfall in higher intensity events, leading to higher rainfall erosivity and high soil loss rates. Nevertheless, agricultural practices and the different structures identified are considered sustainable adaptation strategies to these types of natural risks, qualifying as NbS.